Inaugural lectures of the University Of Malaya - Ibrahim, I. (University of Malaya Library, 1998)
As an academic tradition, professors at the University of Malaya deliver their inaugural lectures which constitute an important milestone in their careers as scholars of academic repute. Sixty-one inaugural lectures, which were delivered from 1959 till 1997 are listed in chonological order and with an author index.